Rapid screening technique for evaluation of maize genotypes against stalk rot complex caused by Macrophomina phaseolina and Fusarium verticilloides - GOPALA, GOPALA; GOGOI, ROBIN; HOODA, K S; RAI, S N; KUMAR, A; HOSSAIN, FIROZ (The Indian Journal of Agricultural Sciences, 2016)
In order to screen maize genotypes for resistance to post-flowering stalk rot (PFSR) complex caused by Macrophomina phaseolina (Tassi) Goid and Fusarium verticilloides (Sacc) Nirenberg under field conditions, toothpick method was used for creating artificial epiphytotics. In this study, 34 maize inbred lines were screened in field by toothpick method of inoculation. Of these accessions, representative 20 maize genotypes were screened by two new methods of inoculation of the cut stems under laboratory condition. Split stems were inoculated in the first method and un-split stems were inoculated by toothpick method in the second. The split method produced recordable data within 15 days of post-inoculation (DPI) where as the un-split stem inoculation method produced result at 20 DPI. Both the new techniques employed in the laboratory were faster in producing results as compared to the field screening of maize genotypes by the standard toothpick method which needs about 40 days for expression of PFSR symptoms. Split open method was better than the un-split method of cut stem inoculation in vitro. A new scale ranging from 1 to 16 cm was developed based on the existing 1-9 scale of PFSR for scoring disease severity in vitro.